2008
DOI: 10.1016/j.pain.2007.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of endogenous analgesia magnitude in a diffuse noxious inhibitory control (DNIC) paradigm: Do conditioning stimulus painfulness, gender and personality variables matter?

Abstract: Descending modulation of pain can be demonstrated psychophysically by dual pain stimulation. This study evaluates in 31 healthy subjects the association between parameters of the conditioning stimulus, gender and personality, and the endogenous analgesia (EA) extent assessed by diffuse noxious inhibitory control (DNIC) paradigm. Contact heat pain was applied as the test stimulus to the non-dominant forearm, with stimulation temperature at a psychophysical intensity score of 60 on a 0-100 numerical pain scale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
300
8
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(350 citation statements)
references
References 38 publications
32
300
8
10
Order By: Relevance
“…The participants were instructed to use a numeric rating scale (NRS) with the extremes: 0 = no pain and 10 = worst pain imaginable. First, the temperature that evoked 60% pain (NRS = 6) for each individual was determined (Granot et al, 2008). The temperature was 32°C at baseline, changed with a rate of 1°C per second, and reached a set temperature plateau that lasted for seven seconds.…”
Section: Supra-threshold Temporal Summation Heat-pain Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants were instructed to use a numeric rating scale (NRS) with the extremes: 0 = no pain and 10 = worst pain imaginable. First, the temperature that evoked 60% pain (NRS = 6) for each individual was determined (Granot et al, 2008). The temperature was 32°C at baseline, changed with a rate of 1°C per second, and reached a set temperature plateau that lasted for seven seconds.…”
Section: Supra-threshold Temporal Summation Heat-pain Testmentioning
confidence: 99%
“…The intention with the procedure was not revealed and participants were told to rate pain every time they felt a change in its intensity. Third, the temperature was increased from the baseline temperature with a rate of 1°C per second and reached a plateau at the NRS-6 temperature for 30 s. The study participants reported pain NRS every time they felt a change in pain intensity, and the ratings at 10, 20 and 30 s were recorded in order to detect temporal summation of pain (Granot et al, 2008).…”
Section: Supra-threshold Temporal Summation Heat-pain Testmentioning
confidence: 99%
“…Because psychological variables may influence pain perception, 13,35 a validated Swedish version of the State and Trait Anxiety Inventory (STAI) was used to assess the level of anxiety. 12 Trait anxiety was assessed at the first session, whereas state anxiety was assessed at all sessions.…”
Section: Anxiety Levelmentioning
confidence: 99%
“…Recently Yarnitsky et al 34 found that the potency of DNIC predicted the development of chronic pain after thoracotomy, indicating that DNIC impairment can be used as a prognostic factor for the development of chronic pain, whereas patients expressing efficient DNIC at the pain-free stage before surgery are less likely to develop chronic postoperative pain and, if having pain, will have less intense pain than those with less efficient DNIC. In a continuation study, 35 it was shown that preoperative DNIC explained 24.6% of the variability in chronic postoperative pain intensity, further suggesting that drugs like sCT, interacting with the descending modulation, may have new applications in patients with chronic pain. sCT has been shown to interact with the opioid receptors with the most prominent agonistic effect on the ÎŽ-and Îș-receptors.…”
Section: Compounds Interacting With the Analgesic Effect Of Calcitoninmentioning
confidence: 99%